Factors influencing purchase intention of organic food among Malaysians in post Covid-19 pandemic: health consciousness as the mediator - Ng, Sing Len (2023)
The World Health Organization (WHO) designated the coronavirus epidemic of 2019, also known as COVID-19, which was initially found in Wuhan, China in November 2019. The global outbreak of coronavirus on March 11, 2020, has caused a shift toward a "new normal" in both societal norms and commercial operations. Nevertheless, there is still a lack of comprehension regarding Malaysian consumers’ preferences and decisions in purchasing goods and services. In this study, a total of 212 valid questionnaires were obtained in order to examine consumer purchase intention toward organic food in the post-pandemic period. The data collection was conducted across entire Malaysia using an online questionnaire approach. The study results showed that health consciousness, subjective norms, and food safety trust influence the organic food purchase intention of Malaysian consumers. Meanwhile, the findings also reveal that health consciousness mediates the relationship between environmental concern, subjective norms, and food safety knowledge with organic food purchase intention during the post-pandemic period. As a result, the study is extremely helpful for organic food industry players in comprehending the purchase behavior of Malaysian consumers in times of post-Covid-19. Therefore, it is believed that greater efforts to spread information about health benefits and food safety among consumers would be supported in encouraging consumer buy intentions of organic food. In addition, the findings of this result will create more chances for a similar research topic to be carried out in the future.